2011
DOI: 10.1007/s10827-010-0310-z
|View full text |Cite
|
Sign up to set email alerts
|

Topologically invariant macroscopic statistics in balanced networks of conductance-based integrate-and-fire neurons

Abstract: The relationship between the dynamics of neural networks and their patterns of connectivity is far from clear, despite its importance for understanding functional properties. Here, we have studied sparsely-connected networks of conductance-based integrate-and-fire (IF) neurons with balanced excitatory and inhibitory connections and with finite axonal propagation speed. We focused on the genesis of states with highly irregular spiking activity and synchronous firing patterns at low rates, called slow Synchronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(91 citation statements)
references
References 52 publications
7
84
0
Order By: Relevance
“…This insensitivity to fine-tuning is due to the homogeneity of the connectivity of individual neurons in this type of networks. The effect has also been observed in a very recent study, where large-scale simulations were performed [42]. In networks with more complex structural elements, like hubs or patches, however, we find that also average correlations depend on details of the connectivity pattern.…”
Section: Introductionsupporting
confidence: 85%
“…This insensitivity to fine-tuning is due to the homogeneity of the connectivity of individual neurons in this type of networks. The effect has also been observed in a very recent study, where large-scale simulations were performed [42]. In networks with more complex structural elements, like hubs or patches, however, we find that also average correlations depend on details of the connectivity pattern.…”
Section: Introductionsupporting
confidence: 85%
“…Indeed, most studies simply ignore w or, at best, they assume that w and b are the same. More recent studies looked into the effect of shared inputs on the network dynamics (which contribute to b ) and found that the membrane potential fluctuations induced by shared inputs are very efficiently canceled by the recurrent network feedback (Renart et al, 2010;Yger et al, 2011;Tetzlaff et al, 2012). However, when we separate the input correlations into within-and between-correlations, it becomes apparent that the single neuron membrane fluctuations are mostly determined by the within-correlations.…”
Section: Discussionmentioning
confidence: 99%
“…The network is topographically arranged in one dimension, with length L, and wrapped onto the circle, to avoid boundary effects. As in previous work4565, the network has local connections defined by a Gaussian spatial profile:…”
Section: Methodsmentioning
confidence: 99%